The role of intestinal flora in metabolic dysfunction-associated steatotic liver disease and treatment strategies - Wang, Li Jun; Sun, Jian Guang; Chen, Shu Cheng; Sun, Yu Li; Zheng, Yang; Feng, Jian Chao (Frontiers in Medicine, 2025)
Metabolic dysfunction-associated steatotic liver disease (MASLD) is a common multi-factorial liver disease, and its incidence is gradually increasing worldwide. Many reports have revealed that intestinal flora plays a crucial role for the occurrence and development of MASLD, through mechanisms such as flora translocation, endogenous ethanol production, dysregulation of choline metabolism and bile acid, and endotoxemia. Here, we review the relationship between intestinal flora and MASLD, as well as interventions for MASLD, such as prebiotics, probiotics, synbiotics, and intestinal flora transplantation. Intervention strategies targeting the intestinal flora along with its metabolites may be new targets for preventing and treating MASLD.